RESPONSE OF SOIL AND FOLIAR APPLICATION OF TION OF MICRONUTRIENTS ON FLOWERING AND FRUITING OF SAPOTA CV. KALIPATTI UNDER HDP SYSTEM - GUVVALI THIRUPATHAIAH; A. M. SHIROL (The Bioscan, 2019)
The present experiment was carried out to find out the response of soil and foliar application of micronutrients on flowering and fruit characteristics of sapota cv. Kalipatti under HDP system at KRCCH, Arabhavi UHS Bagalkot, during 2015-2016. Here three micro-nutrients (namely zinc, iron and boron) were used under this experimentation and the micro-nutrients are applied through soil and foliar spray, for soil and foliar application Zinc and iron sulphates were used,, where as boron sodium tetraborate (Jai bore) for soil application and solubor for foliar application are used. The results indicated that, the foliar application of 0.5% ZnSO4 + 0.5% FeSO4 + 0.3% B tree-1 (i.e. 1st at 50 per cent flowering and another at fruits at pea size) along with recommended dose of macro-nutrients i.e. 100: 40: 150 g NPK and FYM 50 kg tree -1 for four to six years plants was shown less number of days (29 days) taken for flower initiation, flower opening to fruit set (29.50 days), days taken to reach harvestable stage (195.88 days) and the maximum number of flowers ((17.15) and fruits (2.95) shoot -1 , maximum fruit set percentage (23.56%) and fruit retention (85.91%) were recorded. Also it gave superior fruit characters like fruit weight (113.33 g), fruit length (6.10 cm), fruit girth (5.84 cm) and fruit volume (101.50 ml), where as the lowest values were noticed in control.